Identification of a venetoclax-resistance prognostic signature base on 6-senescence genes and its clinical significance for acute myeloid leukemia - Ke, Peng; Xie, Jundan; Xu, Ting; Chen, Meiyu; Guo, Yusha; Wang, Ying; Qiu, Huiying; Wu, Depei; Zeng, Zhao; Chen, Suning; Bao, Xiebing (Frontiers in Oncology, 2023)
Satisfactory responses could be obtained for acute myeloid leukemia (AML) treated by Venetoclax (VEN)-based therapy. However, there are still quite a few AML patients (AMLs) resistant to VEN, and it is critical to understand whether VENresistance regulated by senescence. Here, we established and validated a signature for predicting AML prognosis base on VEN resistance-related senescence genes (VRSGs).In this study, 51 senescence genes were identified with VEN-resistance in AML. Using LASSO algorithms and multiple AML cohorts, a VEN-resistance senescence prognostic model (VRSP-M) was developed and validated base on 6-senescence genes.According to the median score of the signature, AMLs were classified into two subtypes.A worse prognosis and more adverse features were occurred in the high-risk subtype, including older patients, non-de novo AML, poor cytogenetics, adverse risk of European LeukemiaNet (ELN) 2017 recommendation, and TP53 mutation. Patients with high-risk subtype were mainly involved in monocyte differentiation, senescence, NADPH oxidases, and PD1 signaling pathway. The model's risk score was significantly associated with VEN-resistance, immune features and immunotherapy response in AML. In vitro, the IC50 values of rose progressively with increasing expression of G6PD and BAG3 in AML cell lines. The 6-senescence genes prognostic model has significant meaning for prediction of VEN-resistance, guiding personalized molecularly targeted therapies and improving AML prognosis.